Answer:
The answer to your question is: g(3) = 34
Step-by-step explanation:
Function g(x) = 4(x)² - 3(x) + 7
g(3) = 4(3)² - 3(3) + 7 substitution
g(3) = 4(9) - 3(3) + 7 simplify
g(3) = 36 - 9 + 7
g(3) = 36 - 2
g(3) = 34
Equation 1 would be: 3a+2C
Equation 2 would be: 5a+3C
Answer:
26, 27, 28, 29
Step-by-step explanation:
Let the first integer be x.
Then, (x)+(x+1)+(x+2)+(x+3) = 110
=> x+x+1+x+2+x+3 = 110
=> 4x+6 = 110
=> 4x = 110-6
=> 4x = 104
=> x = 104/4
=> x = 26
So, the four consecutive integers are:
1. x = 26
2. x+1 = 26+1 = 27
3. x+2 = 26+2 = 28
4. x+3 = 26+3 = 29
The answer should be: 5/8 x 1/10 = 1/16.